The Effect of Digital Marketing Adoption, Customer Engagement, and Brand Awareness on SME Sales Growth - Andriya Risdwiyanto; Helmi Azahari; Dewi Silvia; Evi Meidasari M (Journal Management & Economics Review (JUMPER), 2026)
The rapid development of digital technology has significantly transformed the way small and medium-sized enterprises (SMEs) conduct their marketing activities and interact with customers. In the digital era, adopting effective digital marketing strategies has become essential for SMEs to enhance competitiveness and achieve sustainable sales growth. This study aims to examine the effect of digital marketing adoption, customer engagement, and brand awareness on SME sales growth. A quantitative research approach was employed using primary data collected through structured questionnaires distributed to SME owners and managers who utilize digital platforms in their marketing activities. A total of 200 respondents participated in the study. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to test the proposed hypotheses. The results reveal that digital marketing adoption has a positive and significant effect on SME sales growth, indicating that the use of digital marketing tools such as social media, online advertising, and digital platforms enhances marketing effectiveness and expands market reach. Furthermore, customer engagement is found to significantly influence sales growth, suggesting that active interaction and relationship-building with customers contribute to higher customer loyalty and increased purchasing behavior. The findings also demonstrate that brand awareness positively affects SME sales growth, as higher levels of brand recognition and familiarity among consumers increase the likelihood of product selection and purchase decisions. Overall, the results highlight the importance of integrating digital marketing strategies, customer engagement initiatives, and brand-building efforts to improve SME performance. This study contributes to the growing body of literature on digital marketing and SME performance while providing practical insights for SME owners and managers seeking to leverage digital technologies to enhance sales growth in the competitive digital marketplace.